1988
DOI: 10.1016/0014-5793(88)80858-5
|View full text |Cite
|
Sign up to set email alerts
|

Polylysine activates and alters the divalent cation requirements of the insulin receptor protein tyrosine kinase

Abstract: Protamine and poly(Lys) activate the protein tyrosine kinase of both the human placental insulin receptor and its purified recombinant cytoplasmic domain. Spermidine, poly(Arg) (average molecular mass 15 kDa), poly(Glu), Arg or Lys are not effective. Activation is stable, reversible, and optimal when the enzyme is preincubated with activator, divalent cation and ATP prior to the addition of exogenous protein substrates. The most striking feature of the activation is that it results in 2&30-fold stimulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 12 publications
(4 reference statements)
2
13
0
Order By: Relevance
“…S6). The activation of insulin signaling by PLL is consistent with the results of previous studies that PLL activates insulin receptor protein kinase by interacting with its β-subunit (Fujita-Yamaguchi et al 1989 ; Rosen and Lebwohl 1988 ). Furthermore, PLL increased the levels of pAkt and pERK compared to treatment with insulin alone when preadipocytes were treated with insulin and PLL at the same time (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…S6). The activation of insulin signaling by PLL is consistent with the results of previous studies that PLL activates insulin receptor protein kinase by interacting with its β-subunit (Fujita-Yamaguchi et al 1989 ; Rosen and Lebwohl 1988 ). Furthermore, PLL increased the levels of pAkt and pERK compared to treatment with insulin alone when preadipocytes were treated with insulin and PLL at the same time (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Cyclic PIP biosynthesis has been described in purified plasma membranes. There may be reservation that activation of cyclic PIP synthase by protamine would be related to activation of a tyrosine kinase, however, it appears most likely that two drugs, protamine and biguanide, which are both shown to activate insulin receptor tyrosine kinase (Rosen and Lebwohl, 1988;Dominguez et al, 1996), would also activate cyclic PIP synthase by tyrosine phosphorylation. The activation of cyclic PIP synthase by fluoride (10 mM) or by GMP-PNP (Figure 3) should be related to activation of the enzyme by G proteins and activation by protamine or biguanides should be related to activation by insulin, as these two compounds are reported to activate the insulin receptor tyrosine kinase (Rosen and Lebwohl, 1988;Dominguez et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Figure 3 shows the concentration-dependent activation of cyclic PIP synthase by the stable GTP-analog GMP-PNP (guanylylimidodiphosphate), a G protein activator (Pfeuffer and Helmreich, 1975). Protamine (Rosen and Lebwohl, 1988) and biguanide (Dominguez et al, 1996) are both known to activate the insulin receptor tyrosine kinase. Furthermore, addition of protamine or biguanide to assays for cyclic PIP synthase activity results in a 4-fold activation of the enzyme, which is additive with respect to the activation by fluoride (10 mM).…”
Section: Kinetic Parameters Of Cyclic Pip Synthasementioning
confidence: 99%
“…Previously, we (11) and others (8,(15)(16)(17) have reported that addition of polycations (such as protamine and poly-L-lysine) to the phosphorylation reaction greatly enhances both the initial velocity of the enzyme and the maximal phosphate incorporation into the soluble insulin receptor kinase domain. It has been demonstrated that the effect of poly-L-lysine is due to a nonspecific kinase aggregation, presumably leading to a more efficient transphosphorylation of the kinases (17).…”
Section: Construction and Purification Of Monomeric And Dimericmentioning
confidence: 98%